Intensitas Aplikasi PSB (Photosynthetic Bacteria) dan Pemberian Pupuk Daun pada Tanaman Buncis (Phaseolus vulgaris L.) - Hamidatun Maulana, Eni; ., Mawardi (Program Studi Agroteknologi, 2023)
Beans are a type of legume that has important nutritional value for healt and has the potential to be developed, both in the lowlands and highlands. Beans contain 2.4 g protein, 0.2 g fat, 7.7 g carbohydrates, as a source of calories and 6.5 g calcium, 4.4 g phosphorus, 1.1 g iron, 630 mg vitamin A, vitamins B1 0.08 mg, vitamin B2 0.01, vitamin B3 0.7 mg, vitamin C 1.90 mg, calories 35 cal and water content 89 grams which greatly affect the quality of public health (Waluyo and Djuriah, 2013). This research was conducted from December 2021 to February 2022, in Pancakarya Village, Ajung District, Jember Regency, East Java. This study used a factorial pattern consisting of two factors with three replications in a randomized block design (RAK). The first factor is type of fertilizer (P) which consists of no fertilizer (P0), NPK fertilizer (P1), and complete fertilizer (P2). The second factor is intensity (I), which consists of PSB once a week (I1) and PSB twice a week (I2). The combination of fertilization consists of PSB Bacterial Culture + NPK Fertilizer and a combination of PSB Bacterial Culture + Complete Fertilizer. The collected data were analyzed by means of variance (Anova), if significantly different, then followed by BNT’s test of 5%. The result showed that the type of fertilizer (P) dan Intensity (I) treatments on the appearance of flowers, number of branches, and fruit weight.